Acoustic radiation force Impulse elastography to aid diagnosis of two canine malignant peripheral nerve sheath tumors - da Cruz, Igor Cezar Kniphoff; Carneiro, Rafael Kretzer; Maronezi, Marjury Cristina [UNESP]; Lima, Bruna Bressianini [UNESP]; Gouveia, Marcelo Cândido Portilho [UNESP]; Uscategui, Ricardo Andrés Ramirez; Minto, Bruno Watanabe [UNESP]; Hörbe, Anna Vitória; Feliciano, Marcus Antônio Rossi (FapUNIFESP (SciELO), 2025)
This report described the use of acoustic radiation force impulse (ARFI) elastography in the diagnosis of two cases of canine malignant peripheral nerve sheath tumors. Both patients presented with lameness in the thoracic limb and no response to previous clinical treatment or trauma history. Physical examination revealed muscular atrophy in one of the thoracic limbs, in both dogs. B-mode axillary ultrasound showed the presence of a predominantly hypoechogenic, heterogeneous, irregular, nonencapsulated nodule with adjacent reactivity, measuring approximately 20.1 mm x 15.4 mm in the first case and 18.3 mm x 10.7 mm in the second. ARFI elastography was performed, showing areas of significant stiffness, with an average shear wave velocity of 4.12 m/s (case 1) and 4.35 m/s (case 2), suggesting malignancy. In both cases, the affected limb was amputated, and the tumors sent for histopathological analysis, which were; subsequently, diagnosed as malignant tumors of the peripheral nerve sheath. The ultrasonographic methods used were essential in the diagnosis and therapeutic conduct.
Elastografia Acoustic radiation force Impulse (ARFI) para auxílio no diagnóstico de dois tumores malignos da bainha dos nervos periféricos caninos
Keywords: ARFI elastography; diagnosis; dog; neoplasm; peripheral nerves